Continued pregnancy and vaginal delivery after 32 weeks of gestation for monoamniotic twins. (November 2015) - Anselem, O.; Mephon, A.; Le Ray, C.; Marcellin, L.; Cabrol, D.; Goffinet, F.
Abstract: Objective: To report the outcomes of 38 monoamniotic twin pregnancies managed homogeneously to assess whether continuing the pregnancy past 32 weeks of gestation and vaginal delivery are reasonable options. Study design: Single-centre retrospective study including all monoamniotic pregnancies managed over a 20-year period at Port-Royal Obstetrics Department, Paris, France. Methods: In the study department, both continuation of the pregnancy up to 36 weeks of gestation and vaginal delivery are allowed for monoamniotic pregnancies in some conditions. Perinatal outcomes are described and then compared according to mode of delivery for patients who gave birth at or after 32 weeks of gestation. Results: Three of the 38 pregnancies included fetal malformations; in two of these cases, both fetuses died in utero at 26 weeks of gestation. In cases without malformations, one twin died in utero in two women at 28.0 and 29.2 weeks of gestation, and both fetuses died in two other women at 24.0 and 24.5 weeks of gestation. Mean gestational age at delivery was 32.9 weeks (range 24.0–36.3). Five women gave birth between 22 and 26 weeks of gestation, six women gave birth between 27 and 31 weeks of gestation, and 27 women gave birth at or after 32 weeks of gestation (26 after excluding those with fetal malformations). No intrauterine or neonatal deaths were observed at or after 32 weeks of gestation. The 28 infants delivered vaginally did not differ significantly from the 22 infants born by caesarean section in terms of umbilical artery pH or 5-min Apgar scores. Conclusion: Continuation of monoamniotic pregnancies beyond 32 weeks of gestation and trial of vaginal delivery are both reasonable options if the parents agree, and optimal surveillance is provided.